Pelatihan Fardu Kifayah Dan Muballigh Di Pimpinan Ranting Muhammadiyah Bandar Khalipah - Muhammad Qorib Qorib; Gunawan Gunawan (University of Muhammadiyah Sumatera Utara, 2019)
In this service is expected to form a concept of guidance to the Muslim community, as Muhammadiyah's next generation who can understand about fardu kifayah. As well as making a simple generation that can prosper, the values of Islam in society. In this training, participants will be able to understand and master about fardu kifayah, which can be developed in society, and teach it back to the public about the real fardhu kifayah. As well as giving birth to talented young da'i, in understanding the true religious knowledge. Therefore, in this dedication we want the future of the generation that will continue the struggle of Muhammadiyah, to educate the Muslim community, and continue the dakwah of muhammadiyah about fardu kifayah which is now a lot of deviations everywhere.